2016
DOI: 10.1063/1.4972033
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic cation diffusion in the GaAs capping of InAs/GaAs(001) quantum dots

Abstract: The effect of the As flux on the kinetics of Ga and In cations, and the role of the elastic strain were studied in the capping process of isolated InAs quantum dots with GaAs by molecular beam epitaxy. Using a fixed evaporation geometry and a suitable choice of growth parameters which enhance the anisotropic diffusion of In and Ga cations, we obtained, at variance with current results, the formation of asymmetric GaAs caps. The growth of a second InAs layer led to the formation of vertically aligned couples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previously to measure the micro-structure uncapped QDs were measured using ARM, 18 however reports in literature suggested that QD shape maybe affected when capped. 19,20 A cross-section of the active region can be examined using TEM, which will enables buried structural information to be seen.…”
Section: Route To New Modelmentioning
confidence: 99%
“…Previously to measure the micro-structure uncapped QDs were measured using ARM, 18 however reports in literature suggested that QD shape maybe affected when capped. 19,20 A cross-section of the active region can be examined using TEM, which will enables buried structural information to be seen.…”
Section: Route To New Modelmentioning
confidence: 99%